THE DATE AND SETTING OF GREGORY OF NYSSA'S COMMENTARY ON THE SONG OF SONGS - Cahill, J. B. (The journal of theological studies, 1981)
J. B. CAHILL; THE DATE AND SETTING OF GREGORY OF NYSSA'S COMMENTARY ON THE SONG OF SONGS1, The Journal of Theological Studies, Volume XXXII, Issue 1, 1 April 19